Janett Morgan. Greek perspectives on the Achaemenid Empire: Persia through the looking glass - Koparal, Elif (Journal of Greek Archaeology, 2016)
Janette Morgan’s ‘Greek Perspectives on the Achaemenid Empire: Persia through the Looking Glass’ is the last book published as part of the series of Edinburgh Studies in Ancient Persia. Almost twenty years after Margaret C. Miller’s ‘Athenians and Persians in the Fifth century BC: A Study in Cultural Receptivity’ was published, one is still in awe of the way that Miller contributed to the debate on cultural receptivity within the context of Greek and Persian engagement.